2008
DOI: 10.1158/0008-5472.can-07-6552
|View full text |Cite
|
Sign up to set email alerts
|

Myc-Mediated Transcriptional Repression by Recruitment of Histone Deacetylase

Abstract: Myc is a transcription factor that features prominently in cancer. The oncogenicity of Myc stems from its ability to regulate expression of genes required for cell growth and proliferation. Although the mechanisms through which Myc activates transcription have been extensively studied, less is known about how Myc represses transcription. Recently, we reported that a conserved element within Myc-MbIII-is important for transcriptional repression. Here, we investigate the mechanism through which MbIII contributes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 22 publications
2
86
0
Order By: Relevance
“…18 MYC can repress protein-coding genes and miRNA by recruiting HDACs, including HDAC3. 5,19 Previously, MYC was reported to repress the miR-15 and let-7 families in B-cell lymphoma, as it was enriched at the promoter regions of these miRNA. 12 Our results, in combination with genome-wide MYC ChIP-sequencing data, 17 indicate that MYC was also present at the promoter regions of the miR-15 and let-7 families in human breast and lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…18 MYC can repress protein-coding genes and miRNA by recruiting HDACs, including HDAC3. 5,19 Previously, MYC was reported to repress the miR-15 and let-7 families in B-cell lymphoma, as it was enriched at the promoter regions of these miRNA. 12 Our results, in combination with genome-wide MYC ChIP-sequencing data, 17 indicate that MYC was also present at the promoter regions of the miR-15 and let-7 families in human breast and lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…As multiple biochemical studies have shown that the two directly interact with each other, we sought to look for the de-repressed targets that may require both BCL6 and HDAC4 in the up-regulated dataset from Eμ-miR-155 mice. Interestingly, one of the key BCL6 target genes, Id2, up-regulation of which inhibits B-cell differentiation, has been proposed to require HDAC4 as one of the repressors (33). Therefore, we propose that BCL6 may recruit HDAC4 to the promoter of Id2 to suppress its transcription.…”
Section: Bcl6 Transcription Is Indirectly Modulated By Mir-155 Througmentioning
confidence: 90%
“…HDACs also facilitate MYC's oncogenic function as a transcription factor, as they are often recruited to the promoter regions of some MYC-targeted genes to facilitate MYC-mediated regulation of transcription. HDAC inhibitors thus decrease MYC gene expression and restore the expression of genes coordinately suppressed by MYC family members and HDACs in multiple cancer cell types, including DLBCL and NMC (19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%